Association between the IL1B −31C > T polymorphism and Helicobacter pylori infection in Asian and Latin American population: A meta-analysis. (September 2015) - Sun, Xudong; Xu, Yuanyuan; Zhang, Fuhua; Jing, Tao; Han, Jian; Zhang, Jinhua
Abstract: Background: Host genetic factors that control the production of cytokines, including interleukin-1β (IL-1β), possibly affect susceptibility to many Helicobacter pylori -related diseases. There is a complex interplay between H. pylori infection, the subsequent production of certain cytokines, and H. pylori- related diseases. We conducted a meta-analysis to clarify the association between the IL1B −31C > T polymorphism and H. pylori infection, and possible subsequent pathogenic mechanisms. Methods: Published literature contained within PubMed, Embase, and the Cochrane Library was used in our meta-analysis. Data were analyzed with the STATA 13.1 software package using pooled odds ratios (ORs) with 95% confidence intervals (95% CI). Egger's regression test, Begg's rank correlation test, and Begg's funnel plot were used to test publication bias. Results: A total of 12 case–control studies comprising 5827 subjects (3335 cases and 2492 controls) were available for our meta-analysis. The IL1B −31C > T polymorphism was associated with an increased risk of H. pylori infection in Asian and Latin American population (TT + CT vs . CC, OR = 1.29, 95% CI = 1.14–1.46; TT vs. CT + CC, OR = 1.23, 95% CI = 1.09–1.39; TT vs. CC, OR = 1.43, 95% CI = 1.22–1.67; T allele vs. C allele, OR = 1.19, 95% CI = 1.10–1.29). A significant association was also found for all genetic models in various subgroups (cancer and no-cancer, hospital- and population-based). Conclusion: Our meta-analysis demonstrated that IL1B −31C > T polymorphism might increase H. pylori infection risk in Asian and Latin American population. Further studies with different ethnicities and larger sample size are required to validate this result. Highlights: Meta-analysis was conducted on association between IL1B −31C > T SNP and Hp infection. Only studies in which serological methods were used to detect Hp were included. IL1B −31C > T SNP increases Hp infection risk in Asian and Latin American population.